Peran Komunikasi Dialogis Guru dan Mitra Didik dalam Pembelajaran di Sekolah Dasar Eksperimental Mangunan - Rian Antony (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2022)
Dialogic communication plays a remarkably substantial role in sustaining good interactions between teachers and students in the shared-learning process inside the class. Within a case study approach, this research explores dialogic communication's role in increasing teacher-student interaction in Eksperimental Mangunan Elementary School's shared-learning process. The research's data collected through in-depth interviews with two teachers and six students combined with external observations. There are three notable findings: the teachers act as a facilitator who helps and motivate students; the teachers act as a midwife who helps students in the shared-learning process; and students act as subjects of open and participatory learners. A comfortable atmosphere in the shared-learning process helps to increase students' participation. This research intended to provide an overview of the importance of applying dialogical communication in the shared-learning process.